The relationship between self-care and quality of life in heart failure patients: a correlational study - Atmanasari , Hesti; Prasestiyo, Hamudi; Wantonoro, Wantonoro (Universitas 'Aisyiyah Yogyakarta, 2025)
Heart failure occurs when the heart is unable to pump blood effectively. As a consequence, the supply of oxygen and nutrients to the body decreases. This condition significantly impacts the patient's quality of life. Effective self-care can help improve the quality of life for patients with heart failure. This study aims to examine the relationship between self-care and quality of life among heart failure patients at the Cardiology Clinic of PKU Muhammadiyah Gamping Hospital. This study employed quantitative, descriptive-correlational design with crosssectional approach. A total of 64 respondents were selected based on inclusion and exclusion criteria using purposive sampling. Data were collected using the Self Care of Heart Failure Index (SCHFI) and the Minnesota Living with Heart Failure Questionnaire (MLHFQ). Data analysis was conducted using the Kendall Tau correlation test. Based on the result, the most of the respondents, 46 (71.9%) showed a moderate level of self-care, and 55 (85.9%) reported a good quality of life. The Kendall Tau test yielded a p-value of 0.002 with a correlation coefficient of 0.388, which indicated a positive and moderately strong relationship between self-care and quality of life. In conclusion, this study shows that there is a relationship between self-care and the quality of life of the heart failure patients. Good self-care improves disease control and patient adaptation, thus having a positive impact on quality of life.